1985
DOI: 10.1002/j.1460-2075.1985.tb03837.x
|View full text |Cite
|
Sign up to set email alerts
|

Actin gene mutations in Drosophila ; heat shock activation in the indirect flight muscles

Abstract: We have identified four mutations affecting the actin III isoform in the indirect flight muscles (IFM) of Drosophila. One mutation does not produce any protein product, and three direct the synthesis of electrophoretic variants of actin. Complementation tests and recombination mapping indicate that all mutations are alleles of an actin gene at chromosomal band 88F (act88F gene). The effect of these mutations is restricted to the IFM. We conclude that the act88F gene is expressed only in the IFM to encode actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
2
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 36 publications
3
67
2
1
Order By: Relevance
“…2 and 6). On the other hand, hsp22 is most abundant among the heat shock proteins in the indirect flight muscle of some flightless mutants (12,19). These mutants express the heat shock genes constitutively as a consequence of a lesion in the gene which encodes the actin that is specifically expressed in the indirect flight muscles (12,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 6). On the other hand, hsp22 is most abundant among the heat shock proteins in the indirect flight muscle of some flightless mutants (12,19). These mutants express the heat shock genes constitutively as a consequence of a lesion in the gene which encodes the actin that is specifically expressed in the indirect flight muscles (12,19).…”
Section: Discussionmentioning
confidence: 99%
“…DNA from flies was prepared essentially as described by Bender et al (4). Extraction buffer (300 pul; 0.1 M Tris hydrochloride [pH 9.0], 0.1 M NaCl, 0.2 M sucrose, 50 mM EDTA, 0.5% sodium dodecyl sulfate) and 12 ,ul of diethylpyrocarbonate were added to 20 flies frozen in liquid nitrogen in an Eppendorf tube and homogenized with a glass pestle. An additional 300 ,ul of extraction buffer was added, and the homogenate was first incubated at 65°C for 30 min and then on ice for 30 min after the addition of 120 ,u1 of 8 M potassium acetate.…”
Section: Methodsmentioning
confidence: 99%
“…We showed previously that two wild-type copies of the MHC gene are required for IFM and TDT function, whereas other muscles fimc tion adequately with a single copy (Mogami et al 1986;O'Donnell and Bemstein 1988). This sensitivity of IFM and TDT function to gene dosage extends to other muscle contractile protein genes as well and has per mitted the isolation of dominant flightless mutations in genes encoding actin and tropomyosin isoforms specific to the IFM (Karlik et al 1984;Hiromi and Hotta 1985;Karlik and Fyrberg 1985).…”
mentioning
confidence: 94%
“…In all three cases the mutation causing flightless phenotype maps to a chromosomal position coincident with the location of the act88F gene. This coincidence, plus the failure by Mogami and Hotta to detect recombination between any of these three alleles and the previously characterized Ifm(3)7 mutation (9,14), suggested that all were act88F alleles.…”
mentioning
confidence: 80%
“…That HSP induction was caused by mutant actin isoforms was supported both by the tissue specificity of the induction, which occurs only within indirect flight muscles (9,14), and by the germ line transformation experiments of Hiromi et al (10), which rigorously established that particular act88F alleles induce HSP accumulation in a dosage-dependent manner. While the full significance of these observations remains to be established, both Okamoto et al (21) and workers in our own laboratory have been impressed by the finding that all act88F alleles which were * Corresponding author.…”
mentioning
confidence: 98%